v-Src-Induced Modulation of the Calpain-Calpastatin Proteolytic System Regulates Transformation - Carragher, N. O. (American Society for Microbiology, 2002)
v-Src-induced oncogenic transformation is characterized by alterations in cell morphology, adhesion, motility, survival, and proliferation. To further elucidate some of the signaling pathways downstream of v-Src that are responsible for the transformed cell phenotype, we have investigated the role that the calpain-calpastatin proteolytic system plays during oncogenic transformation induced by v-Src. We recently reported that v-Src-induced transformation of chicken embryo fibroblasts is accompanied by calpain-mediated proteolytic cleavage of the focal adhesion kinase (FAK) and disassembly of the focal adhesion complex. In this study we have characterized a positive feedback loop whereby activation of v-Src increases protein synthesis of calpain II, resulting in degradation of its endogenous inhibitor calpastatin. Reconstitution of calpastatin levels by overexpression of exogenous calpastatin suppresses proteolytic cleavage of FAK, morphological transformation, and anchorage-independent growth. Furthermore, calpastatin overexpression represses progression of v-Src-transformed cells through the G(1) stage of the cell cycle, which correlates with decreased pRb phosphorylation and decreased levels of cyclins A and D and cyclin-dependent kinase 2. Calpain 4 knockout fibroblasts also exhibit impaired v-Src-induced morphological transformation and anchorage-independent growth. Thus, modulation of the calpain-calpastatin proteolytic system plays an important role in focal adhesion disassembly, morphological transformation, and cell cycle progression during v-Src-induced cell transformation.